(untitled) (International Journal of Engineering and Computer Science, 2025)
The article underscores the need to transition from reactive to proactive risk management amid accelerated digital transformation, where increasing innovation simultaneously heightens dependence on the stability of IT ecosystems. The relevance of the study is determined by the high cost of technology risks and multi-million-dollar losses from outages and SLA breaches, necessitating a comprehensive approach to balancing deployment speed and system reliability. The novelty lies in integrating classical strategic risk-management tools with multi-cloud practices, constructing a dual-channel risk portfolio, and, in the author’s case, abandoning ineffective initiatives and implementing a Smart Onboarding Automation System. The author’s experience demonstrates that automating and standardizing onboarding processes significantly reduces communication-related risks and accelerates the integration of new hires, highlighting how strategic rejection of inefficient practices can enhance stability in complex IT projects.At the same time, the automated onboarding system saves up to USD 1 million per year and frees over 2,200 person-hours monthly on a global scale. The main findings show that a multilayered early-scoping system reduces the likelihood of critical deviations; a dual-channel portfolio simultaneously funds innovation and guarantees operational stability; and the combination of early-warning indicators (EWI), SLA/SLI, and an error budget integrates into the CI/CD pipeline, turning each release iteration into a controlled experiment. Hyper-automation and a culture of shared risk ownership transform risk from a liability into a manageable resource, enhancing financial predictability and accelerating staff adaptation. This article will be helpful to CIOs and PMO leaders.